Lipofibroma of the Uterine Cervix- A Rare Benign Tumor with Brief Review of Literature - Swathi, S; Shanthi, Shanthi; Rao, Nandam Mohan; Sundar, B Syam; Grandhi, Bhavana; boddapati, Amulya (International Journal of Medical Research and Review, 2015)
Lipomas of the uterus are rare and cervical involvement is another rare entity. Approximately 200 cases have been reported in the literature and the incidence ranges between 0.03% to 0.2%. The lesion has lately been discussed interestingly due to its diagnostic confusion with sarcomas on radiographic examination and also due to their disputed histogenesis. We report a case of 36 years old woman presenting with non-specific lower abdominal pain and vaginal discharge who underwent hysterectomy for abnormal pap smear result and an ultrasound diagnosis of a large cyst in the posterior lip of the cervix. Histopathology revealed intramural lipofibroma of the cervix.